Influence of glass forming histories on the structural and thermal properties of tellurite glasses - Araújo, E. B. [UNESP]; Idalgo, E. [UNESP] (My University, 2009)
Tellurite 20Li2O-80TeO2 glasses were prepared with identical nominal composition but with different glass forming histories. Differential scanning calorimetry and x-ray diffraction techniques were used to study the effects of glass forming histories on the thermal and structural properties of these glasses. It was observed that the investigated properties depend strongly on the glass forming histories. XRD results reveals the crystallisation of the γ-TeO2, 7alpha;-TeO2 and α-Li2Te2O2 phases in the studied glasses. DSC results suggested that annealing immediately after quenching at temperatures around Tg and longer times are favorable to produce local ordered regions in the glass without necessarily increasing nuclei number.